Targum song of songs and late Jewish literary Aramaic language, lexicon, text, and translation - Litke, Andrew W. (Leiden Boston Brill, 2019)
Front Matter -- Copyright Page -- Dedication -- Acknowledgements -- Abbreviations -- Introduction -- Phonology and Orthography -- Morphology -- Syntax -- Lexical Stock -- Conclusions and Implications -- Introduction to the Edition -- Transcription and Translation of Paris Héb. 110 -- Back Matter -- Glossary -- Bibliography -- Index of Other Targumic Passages.
In Targum Song of Songs and Late Jewish Literary Aramaic , Andrew W. Litke offers the first language analysis of Targum Song of Songs. The Targum utilizes grammatical and lexical features from different Aramaic dialects, as is the case with other Late Jewish Literary Aramaic (LJLA) texts. The study is laid out as a descriptive grammar and glossary, and in the analysis, each grammatical feature and lexical item is compared with the pre-modern Aramaic dialects and other exemplars of LJLA. By clearly laying out the linguistic character of this Targum in this manner, Litke is able to provide added clarity to our understanding of LJLA more broadly. Litke also provides a new transcription and translation of the Paris Héb. 110 manuscript
Keywords: Bible; Aramaic language -- Grammar; Aramaic language -- Texts